2007
DOI: 10.1179/174328407x226545
|View full text |Cite
|
Sign up to set email alerts
|

Examination of breakdown stress in creep by viscous glide in Al–5·5 at.-%Mg solid solution alloy at high stress levels

Abstract: Creep tests on Al-5?5 at.-%Mg solid solution alloy show that the stress exponent n increases with increasing stress from 3?1 to 5?5. It is demonstrated that the transition to n<5?5 is not consistent either with normal power law breakdown or with a transition to a region of viscous glide controlled by pipe diffusion, but the results are in good agreement with a breakdown of the dislocations from their solute atmospheres. The activation energies for creep at low and high stresses are 136 and 170 kJ mol 21 respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…It is proposed that as carbon atoms diffuse, they drag the pinned dislocations with them and impose solute drag based viscous glide. It is reported in the literature that when stress exponent n = 3, dislocation glide is controlled by the rate of migration of solute atoms that are attached to moving dislocations [31,32]. Therefore, the controlling creep deformation mechanism of the weld joints studied in the present work is proposed to be viscous glide due to the diffusion of carbon.…”
Section: Figure 15mentioning
confidence: 81%
“…It is proposed that as carbon atoms diffuse, they drag the pinned dislocations with them and impose solute drag based viscous glide. It is reported in the literature that when stress exponent n = 3, dislocation glide is controlled by the rate of migration of solute atoms that are attached to moving dislocations [31,32]. Therefore, the controlling creep deformation mechanism of the weld joints studied in the present work is proposed to be viscous glide due to the diffusion of carbon.…”
Section: Figure 15mentioning
confidence: 81%
“…Extensive studies have been conducted to investigate the plastic deformation behaviour of Al2Mg alloys. Graiss and Abd El-Rehim 13 showed that the creep curves of Al-5?5 at.-%Mg solid solution alloy exhibited a transition in creep behaviour controlled by viscous glide to one controlled by high temperature climb at the applied stress corresponding to that at dislocation break away from their solute atmospheres. By means of optical and electron microscopy, Drury and Humphreys 14 found the deformation within the grains occurs by viscous glide in Al-5 wt-%Mg deformed in compression at temperature between 293 and 773 K and flow stresses below 50 MPa.…”
Section: Introductionmentioning
confidence: 99%